Planetary Nebulae and the Ionization of the Interstellar Medium in Galaxies - Stasińska, Grażyna; Trevisan, Marina; Vale Asari, Natalia (Frontiers in Astronomy and Space Sciences, 2022)
We discuss the role of planetary nebulae and their progeny in galaxy context in terms of ionization of the galaxy interstellar medium. This regards ionized gas outside the disk of spiral galaxies, the diffuse ionized medium in spiral galaxies, and the weak line emission of elliptical galaxies.